Waterjetting technology - Summers, David A. (E & FN Spon, 1995)
Waterjet technology is used in a variety of industries including civil engineering, mining, geotechnical engineering, tunnelling, defence, construction and conservation. This book is essential reading for all those engaged in waterjet technology - from manufacturers of the equipment through to Government Contracting Officers who let the awards, to the individual contractors and their engineers.